Managerial leadership and institutional climate to enhance undergraduate education in an Engineering faculty of a Public University in Lima - Alarcón Cubas, José Carlos; Cotrina Gutiérrez, Jesenia Catherine; Rosario Pacahuala, Emilio; Rufino Gabriel, Margarita; Sotomayor Albites, George; Medina Gamero, Aldo; Regalado Chamorro, Mónica (LACCEI, 2025)
The purpose of the investigation was to establish the correlation between the director’s leadership and the institutional climate in an Engineering Faculty of a Public University in Lima. Quantitative, basic descriptive, non-experimental correlational research. Both population and sample included 50 educators from the primary and secondary level. The survey was used as a research method to collect data and the questionnaire was used as an instrument, one per variable, applied individually. The results of Management Leadership indicate that of 100% (N = 50) of teachers surveyed, 96% (n = 48) state that the variable has a good level and those of Institutional Climate indicate that 100% (N = 50) ) of teachers surveyed, 96% (n = 48) state that the variable presents a good level. It has been shown that the manager’s leadership is directly related to the institutional climate, that is, Spearman’s correlation coefficient reaches a positive symbol. At the inference level, the significance value (.017) confirms the existence of a correlation because the calculated value is lower than the theoretically desired value (.05). In this sense, we affirm that there is a correlation between managerial leadership and the institutional climate in a Faculty of Engineering of a Public University in Lima, but the strength of the association is low (.338).